EDUPOL: KAMPANYE ANTI POLITIK UANG DAN HOAKS DI PEKANBARU - Moekahar, Fatmawati; Labellapansa, Ause; Syafhendry, Syafhendry; Qurniawati, Eka Fitri; Rafida, Norhayati; Jabar, Karim Abdul (STAI Darul Qalam Tangerang, 2025)
EDUPOL is a form of political campaign for society of Pekanbaru as an effort to minimize the circulation of money politics and hoaxes ahead of the simultaneous local elections in Riau 2024. The main partners for community service activities are members of Majlis Taklim’s Fastabiqul Khairat Pekanbaru. Partners are considered capable of being agents of change in rejecting money politics and the circulation of hoaxes in society. The activity involved 51 people. Implementation methods are divided into four, namely: Counseling; Application of Technology; Mentoring and Evaluation; and Program Sustainability. The results show that EDUPOL as problem solver by partner with the strongly agree category being 62.7%, while 35.3% were in agree category, and 2% don’t agree. The EDUPOL campaign program makes a positive contribution in increasing public understanding of the dangers of money politics and hoaxes that threaten every election in Indonesia. In the final stage of the program, partners also hope that this program can continue so that it can continue to provide good political education to the community